Efek Antimitosis Biomutagen dari Tanaman Kembang Sungsang (Gloriosa superba L.) pada Pembelahan Sel Ujung Akar Kecambah Cabai Merah Besar (Capsicum annuum L.) - Eti Ernawiati; Sri Wahyuningsih; Yulianty Yulianty (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
Flame lily (Gloriosa superba L.)  is one of the plants containing colchicine, often used as antimitotic compound, in the whole organ. This study aims to gain the combination of extract source  and extract concentration of G. superba capable of inhibit mitosis in root tip cells of chili  sprouts.  The plant is extracted  using the extraction and dilution methods to determine the extract concentration of the treatment. The squash method is used to make a  mitosis preparation. The study is arranged in a factorial using Randomized Complete Block Design (RCBD) with 4 replications. The first factor is extract source:   roots, stems, and leaves. The second factor is the extract concentration: 0, 20.40, 60, and 80%.   The observation shows that the extract of leaf can inhibit mitosis more than exctract of bulbs and roots.  All of the concentration treatment from all extract sources tend to result in similar mitotic index, but significantly different from cells that are not given treatment. The combination of the source extract and concentration of the extract result in varied mitotic index, but  it is obvious that the leaf extract with a concentration of 80% gives the most inhibiting mitosis index: 1.298%.